Principles of corporate finance - Brealey, Richard A. (McGraw-Hill series in finance, 1996)
A presentation of financial theory with in-depth analysis and applications. It presents theory as a way of helping prospective financial managers solve practical problems, and as a way of learning why companies and management act as they do.